The Subtitling and Dubbing of Troy: A Comparative Study - Al Owais, Najla (2012)
A Master of Arts Thesis in Translation and Interpreting (English/Arabic/English) by Najla Al Owais entitled, "The Subtitling and Dubbing of Troy: A Comparative Study." Thesis advisor is Dr. Ahmed Ali and was submitted in June 2012. Available are both hard and soft copies of the thesis.